Risk Analysis of Investment Costs in PPP Projects Using Monte Carlo Simulation - Roihans Muhammad Iqbal; Hari Purwanto (Logic : Jurnal Rancang Bangun dan Teknologi, 2022)
Infrastructure project investment is a substantial urgency in line with the vision of President Jokowi’s administration of developing infrastructure in Indonesia. The Government and Private Sector partnership (PPP) becomes feasible alternative to cover the financial deficit in the provision of infrastructure. The South Jakarta-Cikampek II Toll Road Project has been determined to be operated under the PPP scheme. The identification, allocation, and appropriate risk mitigation of the projects are the important success keys to provide clarity and benefits for among the parties. The purpose of this study is to analyze 27 risk variables from PT PII guidelines qualitatively and quantitatively with probabilistic principles using Monte Carlo simulations, by then accurately to estimate the values of the effect of each risk on the project investment value. The research was carried out by collecting project data, identifying risk variables, questionnaires to experts, risk quantification, Monte Carlo simulation, calculating the effect and value of risk, as well as analysis of risk allocation and mitigation based on the Pareto Principle. The study shows that of 26 influential risk categories and one (1) risk does not affect the investment component of the project. There are 12 Risks could be allocated to the Government and 14 Risks could be allocated to Private Sector. The total value of the amount of risk cost is Rp16,424,331,645,796 (21% of total risk investment value). Based on Pareto, 30% risk categories (equal to 8 risks) are the dominant factors of which equal to 70% of the total value of risk. Hence the mitigation may focus to reduce the dominant factors to lower risk by then decrease the value of risk Rp9,885,627,136,618 that equal to 60% become Rp6.538.704.509.178 (equal to 40% of risk value).